2022
DOI: 10.3390/jmse10070958
|View full text |Cite
|
Sign up to set email alerts
|

ddRAD Sequencing-Based Scanning of Genetic Variants in Sargassum fusiforme

Abstract: Sargassum fusiforme is a commercially important brown seaweed that has experienced significant population reduction both from heavy exploitation and degradation of the environment. Cultivated breed strains are also in a state of population mixing. These population stressors make it necessary to investigate the population genetics to discover best practices to conserve and breed this seaweed. In this study, the genetic diversity and population structure of S. fusiforme were investigated by the genome-wide SNP d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
2
0
0
Order By: Relevance
“…The pantranscriptome showed extensive presence/absence variation, with 69.6% of gene families being variable in willows. This number is similar to the report in a pan-genomic study of 16 sorghum cultivars (64%) [23] but smaller than the pan-transcriptome study of 116 Camellia plants (93%) [53]. As reported in the literature, hybridization and polyploidization are quite common in willow species [9,10], which may cause challenges for pan-genome and pan-transcriptome analysis.…”
Section: Expression Patterns Of Orthologous Genes In Willow Speciessupporting
confidence: 86%
“…The pantranscriptome showed extensive presence/absence variation, with 69.6% of gene families being variable in willows. This number is similar to the report in a pan-genomic study of 16 sorghum cultivars (64%) [23] but smaller than the pan-transcriptome study of 116 Camellia plants (93%) [53]. As reported in the literature, hybridization and polyploidization are quite common in willow species [9,10], which may cause challenges for pan-genome and pan-transcriptome analysis.…”
Section: Expression Patterns Of Orthologous Genes In Willow Speciessupporting
confidence: 86%
“…The analysis of GC content and microbial community has shown that compared with the change in the environment, the effect of genetic information is still limited. Our previous study also showed low genetic diversity within and between S. fusiforme populations [38]. The structure of the S. fusiforme microbiome did not change much in the seawater environmental state after 10 days, which supports the difficulty of degradation in the natural state.…”
Section: Discussionsupporting
confidence: 60%